2020
DOI: 10.1080/17441692.2020.1867880
|View full text |Cite
|
Sign up to set email alerts
|

Crisis management in authoritarian regimes: A comparative study of COVID-19 responses in Turkey and Iran

Abstract: The new coronavirus disease, or COVID-19, was first identified in late 2019 and declared as a pandemic by the World Health Organization (WHO) in March 2020. Turkey and Iran have been heavily affected by the outbreak, with over 460,000 and 890,000 cases reported respectively, so far. Even though these two countries have similar political and ideological approaches and are roughly the same size in terms of population density, as well as despite a high number of reported COVID-19 cases, a fast infection spread ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 14 publications
0
21
0
1
Order By: Relevance
“…It does not appear to be true. By analyzing the performance of Iran and Turkey in dealing with the COVID-19 crisis, some scholars argue that Turkey did a “better” job than Iran in responding to the COVID-19 public health crisis ( 28 ). Even though most authoritarian governments are more likely to institute strict censorship of major media, they try to control the flow of news and information to the public ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It does not appear to be true. By analyzing the performance of Iran and Turkey in dealing with the COVID-19 crisis, some scholars argue that Turkey did a “better” job than Iran in responding to the COVID-19 public health crisis ( 28 ). Even though most authoritarian governments are more likely to institute strict censorship of major media, they try to control the flow of news and information to the public ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…What is the situation in terms of the current public health crisis? Studies have found that authoritarian governments usually present themselves as more successful in controlling the spread of disease ( 28 ). Hofstede's cultural dimension of individualism vs. collectivism can serve as a powerful explanation for the difference in effectiveness of crisis response between Asian countries, which emphasize collectivism, and Western countries, which espouse individualism ( 29 , 30 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The prime reason for the relative success of Turkish government in its fight with COVID-19 pandemic would be the fact that the Presidential Government System allows the health bureaucracy and other institutions to act in a coordinated manner. Some other factors impacting on this result include economic differences between Turkey and Iran, relatively strong financial position of Turkey and the fact that Turkey has had more health resources such as intensive care unit, medical equipment and test kits (43). Another study evaluating Turkey's strategies against COVID-19 pandemic has revealed that, the reasons for this success can be attributed to measures taken in order to maintain social distance among citizens, travel ban on visitors from high risk countries; quarantine measures for citizens returning from such countries; and the implementation of various restrictions such as the closure of educational institutions, shopping centers and entertainment venues.…”
Section: Pandemics and Political/administrative Systemmentioning
confidence: 99%
“…Вынужденная изоляция граждан и закрытие большинства предприятий осложнило общую экономическую деятельность. Наиболее емко предпринятые государством меры по борьбе с короновирусом представлены в работах Л. Джина, С. Сана, М. Бастуга и Х. Басли (Jin, 2020;San, Bastug, Basli, 2020).…”
Section: результатыunclassified